LMNB1 regulates breast cancer cell senescence and migration through PPAR signaling pathway - Shaoda Meng; Sicheng Liu; Chunsheng Liu; Kunxian Yang; Minghua Lai (Discover Oncology)
Abstract Breast cancer is the malignant tumor with the highest incidence in the world. LMNB1 is an important component of the nuclear backbone. LMNB1 is abnormally highly expressed in breast cancer, but its role in tumors still needs to be comprehensively studied. In this study, we overexpress and knockdown LMNB1 in breast cancer cells and explore the effects of LMNB1 on cell proliferation, senescence, migration, and underlying mechanisms. We analyzed the expression level of LMNB1 in breast cancer and its clinical relevance utilizing bioinformatics methods, qRT-PCR, and western blot. To elucidate the effects and mechanisms of LMNB1 on breast cancer cells, we performed SA-β-gal staining, CCK-8, colony formation, wound healing, and Transwell assays in breast cancer cells with LMNB1 overexpression and knockdown, and then examined the expression of relevant genes and proteins. In addition, we also analyzed the signaling pathways regulated by LMNB1 with the help of bioinformatics tools. Overexpression of LMNB1 significantly inhibited the senescence of cancer cells and promoted cell proliferation, migration, and invasion. The opposite results were obtained in LMNB1 knockdown cells. LMNB1 inhibited the PPAR signaling pathway in breast cancer. Our study suggests that LMNB1 is a novel therapeutic target in breast cancer.